PEMANFAATAN POS PEMBINAAN TERPADU PENYAKIT TIDAK MENULAR (POSBINDU PTM) OLEH WANITA LANSIA DALAM RANGKA MENCEGAH PENYAKIT TIDAK MENULAR DI WILAYAH KERJA PUSKESMAS CILONGOK 1 - Fauzia Purdiyani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Based Buletin jendela data Informasi kesehata lansia, in Indonesia in 2010 there were 18.1 million elderly people.WHO data show that 36 million deaths of elderly people due to non-communicable diseases. Posbindu PTM launched a program for the early detection of disease is not contagious but the fact these facilities are utilized by risk groups (elderly women). The main purpose of this research is to analyzeefactors related to the utilization factor Posbindu PTM by elderly women. The method used quantitative with cross sectional approach. The total population of 398 elderly women with a total sample of 82 women using proportional stratified random sampling techniques. The analysis of the data using analysis of univariate statistical tests with bivariat and Chi Square (0.05 significant levels). Results of the study showed no relationship between age (0,913),eduacation stage (0,155) and accessibility (0,052), while the jobs respondents (p=0,025 ), status of the treatment of the respondent (p=0,021), health status, knowledge, attitude, support health cadres (p=0,000), support health care personnel and peers (p=0,002 ), family support (p=0,003), the perception of pain (p=0,004 ) and needs Posbindu PTM (p=0,001) has value p-value ≤ α (0.05) so that it can be concluded that there is a relationship between variables with the utilization of elderly women by  Posbindu PTM. The advice of this research is to carry out monitoring and evaluation of the implementation of the PTM Posbindu each month towards the performance of the health workforce and health cadre, make colobaration between Posyandu lansia program and Posbindu PTM.